Analysis of Kinematic Characteristic of the Arc Cutting Reciprocating Saw based on Curve Face Gear Pair - Jinhan Xin; Chao Lin; Weishan Yan; Jialiang Liu; Chunjiang He (Jixie chuandong)
Aiming at the sawtooth cutting mechanism of traditional reciprocating saw, a new type of kinematic mechanism of arc cutting reciprocating saw with curve face gear pair is proposed. By using the meshing and coordinate transformation principle of curve face gear pair, and combining with mechanical principle, gear meshing theory and modern design method, the transmission coordinate system of the compound kinematic mechanism with curve face gear pair and connecting rod is established, the motion equation of the compound kinematic mechanism is deduced, the influence of displacement, velocity and acceleration on the compound kinematic mechanism of arc cutting reciprocating saw and its variation law are analyzed. By using the software of SolidWorks and Adams, the kinematic simulation model of the arc cutting reciprocating saw is established, the kinematic characteristic law of the reciprocating saw is obtained. The corresponding experimental bench is built and tested, and the theoretical simulation data and experimental results are compared with the theoretical analysis results to verify the feasibility of the reciprocating saw mechanism with curved gear pair at the end. The corresponding experimental bench is built and the test is carried out, and the theoretical simulation data and experimental results are compared with the theoretical analysis results, the feasibility of the arc cutting reciprocating saw mechanism with curve face gear pair is verified.